An Analysis of Loess Tunnel Failure and Its Mechanism - Shuai Shao; Shengjun Shao; Jun Li; Bing Qiu (Advances in Civil Engineering)
A series of changes of mechanical properties such as fracture development, relaxation, collapse deformation, and strength decreasing of the surrounding rock of loess tunnels occur due to shearing and immersing, and loess tunnels will be prone to engineering failures, including large deformation, fissure, ground collapse, landslide, and lining cracking, seriously threatening the construction and operation safety of tunnels. These problems are especially prominent for long-span loess tunnels. Based on the understanding of features in the construction and operation of the loess tunnel project and proceeding from the perspective of structural evolution of loess, distribution of the shear deformation zone, instability of the excavation face, and adverse effects of geological conditions, the predisposing factors of damage of the surrounding rock and the supporting structure of large-span loess tunnels, common types of failures, and their formation mechanisms are analyzed in this paper. According to the relationship between the evolution of the loess structure and the law of strength change, an improved Mohr–Coulomb elastic-plastic, tension-compression-shear, constitutive model, considering the loess structural property, is established and applied in numerical calculation. The formation mechanism of different failures in the course of loess tunnel construction is revealed by numerical analysis, in which the structural property of loess, loess strata, geological conditions, and excavating and supporting actions are simulated by the numerical method. A reference is provided for the prevention and remediation of engineering failures of a loess tunnel.